2010
DOI: 10.3758/s13414-010-0010-9
|View full text |Cite
|
Sign up to set email alerts
|

Crossmodal duration perception involves perceptual grouping, temporal ventriloquism, and variable internal clock rates

Abstract: Here, we investigate how audiovisual context affects perceived event duration with experiments in which observers reported which of two stimuli they perceived as longer. Target events were visual and/or auditory and could be accompanied by nontargets in the other modality. Our results demonstrate that the temporal information conveyed by irrelevant sounds is automatically used when the brain estimates visual durations but that irrelevant visual information does not affect perceived auditory duration (Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
71
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 65 publications
(117 reference statements)
12
71
3
Order By: Relevance
“…This result, in accordance with previous studies (e.g., Klink et al, 2011;Shams, Kamitani, & Shimojo, 2000, suggests that the auditory stimulus altered the perception of the visual stimulus when the two synchronously presented stimuli were incongruent in duration.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This result, in accordance with previous studies (e.g., Klink et al, 2011;Shams, Kamitani, & Shimojo, 2000, suggests that the auditory stimulus altered the perception of the visual stimulus when the two synchronously presented stimuli were incongruent in duration.…”
Section: Discussionsupporting
confidence: 82%
“…Note that the results of Experiment 1 are consistent with the outcome of a recent study reported by Klink et al (2011), who showed that the perceived duration of a visual stimulus depended on the duration of an auditory stimulus presented synchronously. Accordingly, given that audition dominates vision in the processing of temporal information, we argue that perceived visual duration in our study was biased towards the perceived duration of the auditory input (e.g., Romei, De Haas, Mok, & Driver, 2011;Shams et al, 2000Shams et al, , 2002Walker & Scott, 1981).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The former occurs when perceived visual duration is pulled in the direction of concurrently presented-but physically discrepant-auditory durations (Chen & Yeh, 2009;Klink, Montijn, & van Wezel, 2011). The latter arises when recent sensory history contains consistent duration information.…”
Section: Introductionmentioning
confidence: 97%